2017
DOI: 10.1002/jctb.5364
|View full text |Cite
|
Sign up to set email alerts
|

A short review on the research progress in alfalfa leaf protein separation technology

Abstract: Alfalfa leaf protein constitutes an important food ingredient and is widely used in food technology. Due to high nutritive value and high proteins content, alfalfa is widely used in animal and human food. Conventionally, industrial leaf protein production from alfalfa requires complex processing and high separation temperature (90 °C), which causes high energy cost, release of sensitive elements and protein denaturation. To overcome these issues, developing novel separation technologies with low energy consump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Alfalfa ( Medicago sativa L.) has one of the highest feeding values of leguminous forages (Zhang et al ., 2017), and is an excellent feed ingredient preserved as hay, haylage or silage for lactating dairy cows (Schmidt et al ., 2009). In comparison with grasses, it has a higher content of crude protein (CP), greater concentration of organic acids and minerals; however, it is difficult to ensile due to its high buffering capacity for acidic conditions, in combination with the low water-soluble carbohydrates (WSC) concentrations (McDonald et al ., 1991; Ogunade et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Alfalfa ( Medicago sativa L.) has one of the highest feeding values of leguminous forages (Zhang et al ., 2017), and is an excellent feed ingredient preserved as hay, haylage or silage for lactating dairy cows (Schmidt et al ., 2009). In comparison with grasses, it has a higher content of crude protein (CP), greater concentration of organic acids and minerals; however, it is difficult to ensile due to its high buffering capacity for acidic conditions, in combination with the low water-soluble carbohydrates (WSC) concentrations (McDonald et al ., 1991; Ogunade et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite those distinguished features, HPTFF is vulnerable to bigger MWCO membrane. This trend was confirmed by Zhang et al that testing UF rotating disk membrane (UF-RDM) for separation and concentration of leaf protein from alfalfa juice [23,145,146]. Higher MWCO and temperature was attributed to aggravating irreversible fouling and separation performance during VRF = 6 and VRF = 12, but also to leveraging better filtration behavior and productivity.…”
Section: High-performance Tangential Flow Filtration (Hptff)mentioning
confidence: 61%
“…Heat precipitation yielded the lowest precipitation yield, on average 33.5%, whereas isoelectric precipitation at pH 4-4.5 precipitated 34.0%. Based on the average isolectric point of all proteins in green juice, the optimum for isolectric precipitation is typically pH 4-4.5 (Santamaría-Fernández et al, 2017;Zhang et al, 2017). The results obtained here revealed that precipitation at a lower pH of 2.5, i.e., the pH used for lignosulfonate precipitation, gave a small improvement of the precipitation by 4%.…”
Section: Loading Experiments From Ryegrass-clovermentioning
confidence: 71%
“…A key step in the green biorefinery is the protein separation. Typically, the green biomass is fractionated into two different fractions by pressing in e.g., a screw press (Zhang et al, 2017;Corona et al, 2018a). One fraction is the pulp, which contains fibers along with insoluble and fiber bound proteins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation